If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 6) = 12 + 2x Reorder the terms: 2(6 + x) = 12 + 2x (6 * 2 + x * 2) = 12 + 2x (12 + 2x) = 12 + 2x Add '-12' to each side of the equation. 12 + -12 + 2x = 12 + -12 + 2x Combine like terms: 12 + -12 = 0 0 + 2x = 12 + -12 + 2x 2x = 12 + -12 + 2x Combine like terms: 12 + -12 = 0 2x = 0 + 2x 2x = 2x Add '-2x' to each side of the equation. 2x + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 0 = 2x + -2x Combine like terms: 2x + -2x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| ln(2x^4+10x^3)+ln(1/(3x^3)) | | 7-6=12-2x | | 0=cx-a+b | | cx-a+b=2b | | 5x+-10=21-6x | | 9+x/2=10 | | 1x-4y=-27 | | y=5sinx+3x | | -4x/3=12 | | 355-5x=0+5x | | -3/4y+2=14 | | -2(3n-1)-n=5(n-4) | | 6/5+x=4/7 | | 120+10x=15+4x | | 2x+(2*2*x+5)=949 | | x-52=194 | | 5*5x=8*5 | | 6x-28=x-8 | | 3x+(2*2*x+5)=949 | | 10n+15=54n+48+4 | | 3[2x-9]-10=-17 | | 2(7-3r)=3r-22 | | (4/(x-5))+(3/(x+4)) | | 14x^2-6x^3=0 | | 9(4-y)/5=-y | | 8v-2+2(2v+2)=-2(v+5) | | 2x+15=4x-15 | | =12s^2-17s-5 | | 5y+11=51 | | x-4/5=6/5 | | 5*2x=6*5 | | 4a+7b+3a-2bfora=5 |